Uptake of Ni(II), Eu(III) and Pu(III/IV) by Hardened Cement Paste in the Presence of Proxy Ligands for the Degradation of Polyacrylonitrile - Szabo, P. G.; Tasi, A. G.; Gaona, X.; Maier, A. C.; Hedström, S.; Altmaier, M.; Geckeis, H. (Frontiers in Nuclear Engineering, 2023)
The uptake of 63Ni(II), 152Eu(III) and 242Pu(III/IV) by hardened cement paste (HCP, CEM I) in the degradation stage II (pH ≈ 12.5, [Ca] ≈ 0.02 M) was investigated in the absence and presence of α-hydroxyisobutyric, 3-hydroxybutyric and glutaric acids. These organic ligands were previously identified as proxies for the degradation products of UP2W (a polyacrylonitrile-based material used as filter aid in nuclear power plants) under repository conditions. Sorption experiments were conducted with various ligand concentrations (10–4 M ≤ [L]tot ≤ 0.1 M) and solid-to-liquid ratios (0.5 gdm–3 ≤ S:L ≤ 20 gdm–3). Redox conditions in the Pu systems were buffered with either hydroquinone (HQ, pe + pH ≈ 10) or Sn(II) (pe + pH ≈ 2). Strong sorption is observed for 152Eu(III) and 242Pu(III/IV) in the absence of proxy ligands, with distribution coefficients (log Rd ≈ 2.2–4, with Rd in m3kg–1) in line with data reported in the literature. No differences are observed for sorption experiments with Pu in HQ and Sn(II) systems. Lower Rd values are determined for 63Ni(II) (log Rd,63Ni ≈ 0–1), consistently with previous studies. In combination with log Rd,natNi ) determined on the basis of the concentration of natNi(II) in pristine HCP and in cement porewater, values of the partition coefficient (alfa) close to 1 are determined. This suggests that the uptake of 63Ni is possibly driven by isotopic exchange with the complete species inventory of natNi present in pristine HCP, including Ni in solid phases and associated with surfaces, e.g. of C-S-H phases. The presence of proxy ligands has a negligible effect on the uptake of 152Eu(III) up to [L]tot = 0.1 M. A slight decrease in the distribution ratios for 63Ni(II) and 242Pu(III/IV) is observed at [L]tot > 10–2 M, although the effect is less evident in the case of plutonium due to the dispersion of the data and the increase of the detection limits with increasing ligand concentrations. Compared to strongly complexing ligands like isosaccharinic acid or gluconate, the investigated proxy ligands show a minor capacity for radionuclide mobilization in cementitious systems, even at high concentrations.